Geotechnical and geological model applied to crushing processes in open pit mines - Peña, P; Fuenzalida, R; Villarroel, R; Merino, P; Tapia, M; Casanova, P (Slope Stability 2013: Proceedings of the 2013 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2013)
The geotechnical model for pit stability in Carmen de Andacollo (CDA) deposit does not offer a good interpretation to predict or explain the rock behaviour in the crushing process. This work proposes a modification to the database analysis and geotechnical characterisation to create a three-dimensional model that can predict and explain the rock behaviour in this process. Two lines where followed to develop this work: 1) define particle size results after blasting, according to the geological conditions; and 2) define the intact rock behaviour in the crushing. Considering the geotechnical tests to characterise the intact rock, the tensile test (Brazilian test) is the one that best correlates with the crushing process. This test breaks the rock through tensile stress, however at the moment of this study, there was scarcity of this type of test and it had a low representativeness in the deposit. Hence, the point load test (PLT) was selected because it was the most representative parameter available; at a low cost and in addition, it is an indirect measurement of the tensile strength. The following defined the particle size characteristics of the rock mass after blasting: mesh through which 50% P(50) and 80% P(80) of the blasted material passed and the percentage of pieces smaller than 67 mm, between 67–100 and >100 mm. This information has different meshes and was assessed in function of lithology, geotechnical unit and mineral zone. This analysis allowed choosing four parameters to define the rock mass crushability. Point load strength PLT(IS(50)) corresponds to a strength index where two tapered points are buried in the rock specimen opening it by tensile stress. The purpose of using PLT is to use the trends generated with this test to assess the general rock’s stress strength. Mineral zone is relevant in the behaviour of the particle size and strength of the intact rock as it establishes the level of weathering or the environmental effect on the rock. Rock quality designation (RQD) is an indirect indicator of in situ particle size of the rock mass as it measures the percentage of diamond drill cores larger than 10 cm per drilled section. In this case, RQD was the best-distributed geotechnical parameter available for the deposit. Hydrothermal alteration characteristics complement the information provided by the mineral zone. That is how the siliceous alterations create a significant increase in tensile strength and in the rock’s compressive strength, while some alterations such as the argillic alteration or presence of oxidation are associated to an increased weakness in the strength properties of the intact rock. According to the results of this first model of the CDA crushability index (CI), classes 1 and 2 are defined as soft to very soft rocks, which could cause troubles as they are highly altered rocks with a plastic behaviour that can generate too much fine material. Classes 3 and 4 are considered as normal rocks, and classes 5 and 6 are considered of very hard type, which can cause performance troubles in the crusher throughput. This screening system defined is a first approach to solve the problem, which must continue being studied based on the crushability results for rock mass units that have previously defined ratings.